Properties of Lithium bis(oxatlato)borate (LiBOB) as a Lithium Salt and Cycle Performance in LiMn2O4 Half Cell - Sai Wang, Weihua Qiu, Tao Li, Bitao Yu, Hailei Zhao (International Journal of Electrochemical Science)
Crystalline LiBOB which we prepared in our lab was observed by SEM method. Impurities of product were examined by XRD experiment. The decomposition voltage under a deoxidized current was 1V vs.Li+/Li, and under a oxidized current the electrochemical stabilities is up to 5V vs.Li+/Li. The conductivity of two kinds of LiBOB based electrolytes were both lower than that of LiPF6 based electrolyte. Through galvanostatic cycling test of the half cells it could be observed that LiBOB cell has a better capacity retention than that of LiPF6 cell.